UMP donates 100 Mandarin books to school students - Mimi Rabita, Abdul Wahit (2023)
MARANG, May 30, 2023 - The Confucius Institute (CI) of Universiti Malaysia Pahang (UMP) has donated 100 Mandarin books, videos, and dictionaries to Yayasan Terengganu Imtiaz Secondary School Marang, in an effort to assist the students in mastering the Mandarin language.